Construction of 3D interconnected boron nitride/carbon nanofiber hybrid network within polymer composite for thermal conductivity improvement. (1st June 2023) - Cui, Yexiang; Xu, Fei; Bao, Di; Gao, Yueyang; Peng, Jianwen; Lin, Dan; Geng, Haolei; Shen, Xiaosong; Zhu, Yanji; Wang, Huaiyuan
Highlights: A mechanically strong 3D BN-CNF scaffold was constructed by salt template method. The prepared 3D networks can provide effective heat transfer pathways. A hetero-structure was in situ formed between the 1D CNF and 2D BN within the 3D networks after the carbonization. 3D networks filled EP composites demonstrate strong heat dissipation performance. Abstract: With the increasing power density and integration of electronic devices, polymeric composites with high thermal conductivity (TC) are in urgent demand for solving heat accumulation issues. However, the direct introduction of inorganic fillers into a polymer matrix at low filler content usually leads to low TC enhancement. In this work, an interconnected three-dimensional (3D) polysulfone/hexagonal boron nitride-carbon nanofiber (PSF/BN-CNF) skeleton was prepared via the salt templated method to address this issue. After embedding into the epoxy (EP), the EP/PSF/BN-CNF composite presents a high TC of 2.18 W m −1 K −1 at a low filler loading of 28.61 wt%, corresponding to a TC enhancement of 990% compared to the neat epoxy. The enhanced TC is mainly attributed to the fabricated 3D interconnected structure and the efficient synergistic effect of BN and CNF. In addition, the TC of the epoxy composites can be further increased to 2.85 W m −1 K −1 at the same filler loading through a post-heat treatment of the PSF/BN-CNF skeletons. After carbonization at 1500°C, the adhesive PSF was converted into carbonaceous layers, which could serve as a thermally conductive glue to connect the filler network, further decreasing the interfacial thermal resistance and promoting phonon transport. Besides, the good heat dissipation performance of the EP/C/BN-CNF composites was directly confirmed by thermal infrared imaging, indicating a bright and broad application in the thermal management of modern electronics and energy fields. Graphical abstract: Image, graphical abstract